233k views
9 votes
Solve each equation. 7(x+4)-6(x+3)=x+5

User VietDD
by
5.1k points

2 Answers

6 votes

Answer:

7(x+4)-6(x+3)=x+5

or , 7x + 28 - ( 6x + 18 ) = x + 5

or , 7x + 28 - 6x - 18 = x + 5

or , x + 10 = x + 5

The equation is incorrect !!

User Lydon
by
5.6k points
1 vote
Answer:

7(x+4)-6(x+3)=x+5

We simplify the equation to the form, which is simple to understand
7(x+4)-6(x+3)=x+5

Reorder the terms in parentheses
+(+7x+28)-6*(x+3)=x+5

Remove unnecessary parentheses
+7x+28-6+*(+x+3+)=+x+5

Reorder the terms in parentheses
+7x+28+(-6x-18)=x+5

Remove unnecessary parentheses
+7x+28-6x-18=+x+5

We move all terms containing x to the left and all other terms to the right.
+7x-6x-1x=+5-28+18

We simplify left and right side of the equation.
0x=-5

0=-5

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

(hope that helps you out :)
User Gzimmers
by
5.2k points